PERSEPSI PESERTA DIDIK KELAS X MENGENAI PEMBELAJARAN DARING PADA MATA PELAJARAN SEJARAH DI SMK NEGERI 3 PONTIANAK - Josse Batistuta Hutauruk; Andang Firmansyah; Edwin Mirzachaerulsyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This research aims to find out how students perceive online learning in history subjects. Data collection techniques used in this study were observation, interviews, and also documentation. As for the data collection tools using observation guidelines, interview guidelines and also documentation studies. To test the validity of the data, the author uses the technique of extended observation and triangulation. The results of the study show that: (1) Students understand what is meant by online learning, so that in carrying out their learning they have used various kinds of application media in supporting the teaching and learning process such as Google Classroom, Google Meet, Zoom, and Whatsapp. During the online learning process, not all students experience a calm learning situation. Some students feel that when learning takes place, they experience a noisy learning situation due to the sound of passing vehicles and the many family activities at home so that they do not focus on learning. In the online learning process, teachers have not used online lesson plans. So that in the process of implementing learning the teacher continues to make adjustments. (2) In online learning, the obstacles encountered are signal problems, limited quotas, and a less conducive learning environment.Keywords : History Learning, Online Learning, Student Perceprion